Pengaruh Kewibawaan Guru Fikih terhadap Aktivitas Belajar Siswa di Madrasah Tsanawiyah Miftahul Huda Seberang Tembilahan Kecamatan Tembilahan - Syahid, Abd.; Ilyas, M.; Zulkarnainsyah, Zulkarnainsyah; Hidayat, Suriya (Asatiza: Jurnal Pendidikan, 2023)
This study aims to determine whether there is an influence of Jurisprudence Teacher Authority on Student Learning Activities. This type of research is quantitative research. The number of samples in the study amounted to 71 people. Data collection techniques through questionnaires and documentation. The data analysis technique was carried out by means of a simple linear regression statistical test. Based on data analysis on variable X, namely the Authority of the Fikih Teacher, the result is 97% and is categorized as Very Strong, because it lies in the Interval Criteria of 81% -100%. Furthermore, based on data analysis on the Y variable, namely Student Learning Activities, the results obtained were 97% categorized as Very Strong, because it lies in the Interval Criteria of 81% -100%. Based on data analysis on variables X and Y, namely the effect of the authority of the Fikih teacher on student learning activities, the results obtained are F count ≥ F table = 69.5 ≥ 3.99, so reject Ho and accept Ha means that there is a positive and significant influence between the authority of the Fikih teacher on Student Learning Activities.